Microsurgical Semilunar Bilaminar Technique Halts Progression of Marginal Tissue Recession by Soft Tissue Phenotypic Modification—A Case Report With 3‐Year Follow‐Up - Saravanan Sampoornam Pape Reddy; Delfin Lovelina Francis; Manish Rathi; Ruchi Harish; Ravikiran Narayana; Balaji Manohar; Shaili Pradhan (Clinical Case Reports)
ABSTRACT Phenotype modification therapy using the novel semilunar flap with xenogeneic collagen matrix improves gingival phenotype, root coverage and increased keratinized tissue width. It also halts the progression of recession, enhances tissue resilience and improved plaque control sustainable over 3 years. Collagen matrix avoids second site surgery and hence less morbidity.